Simultaneous LC-MS/MS Determination of Racemic Warfarin and Etravirine in Rat Plasma and Its Application in Pharmacokinetic Studies - John, Jyothy; Robinson, Keila; John, Mathew; Caballero, Jason; Ma, Jing; Liang, Dong; Abobo, Cyril (IntechOpen, 2012)
None